Relationship Between Cancer Response Style, Metacognition, and Anxiety of Breast Cancer - İlayda Cebeciler; Esra Savaş (Sakarya Üniversitesi Kadın Araştırmaları Dergisi)
One of the main purposes is to examine the relationship between cancer response style, metacognition, and anxiety of newly diagnosed and remission breast cancer patients based on the metacognitive model. Second is to evaluate difference between newly diagnosed and remission breast patients in manner of cancer response style, metacognition, and anxiety levels. A total of 110 early-stage breast cancer patients (56 newly diagnosed, 54 in remission) from one of the government hospital in Türkiye, Muğla were enrolled from November 2022 to August 2023. The participants completed sociodemographic and medical information, the Metacognition Scale (SBS-30), Cancer Response Style Scale, and Generalized Anxiety Scale-Revised (GADS-R). The average scores of the participants on the Generalized Anxiety Scale were determined as 1591,12 ± 282,62, in those who were in newly diagnosed and was determined 1284.44 ± 445.34 in remission. Anxiety has a positive correlation with metacognitive activity and emotion-oriented strategies (P<0.05); while fighting spirit and distrust of cognitive activities were negatively correlated (P < 0.05). Anxiety was a common phenomenon in newly diagnosed breast cancer patients and average during the remission stage. In addition, both cancer responses and metacognitive beliefs had a direct and indirect association with the occurrence and development of anxiety. Moreover, positive, and negative metacognitions had different mechanisms on anxiety in patients with breast cancer.